RADIATIONS EFFECTS IN CARBON NANOSTRUCTURES - Ilyin, A.M.; Daineko, E.A. (Recent Contributions to Physics, 2018)
It was made the formation of nanotubular elements, containing the radiation structure defects and was determined the energetic and structure characteristics of some possible defects configurations, which provide the rigid bond between them. It was shown that radiation influence can induce the appearance of particular kind of radiation defects – bridge configurations, which create the strong bonds between nanotubular elements. This effect can be used in various nanotechnologies. For example, creation of light and durable composit materials on the base of matrix from light metal alloys and rigid nanotubular insertions.